Adapting to Adversity: Effects of COVID-19 on Parenting in Chile - Pérez, J. Carola; Aldoney, Daniela; Vivanco-Carlevari, Anastassia; Coo, Soledad; Guzmán, Eugenio J.; Silva, Jaime R. (Frontiers in Psychology, 2022)
The pandemic outbreak in March 2020 with the related sanitary regulations and restrictions implied an abrupt and significant change for society in general and families’ organization in particular. In Chile, by this time the metropolitan district was under a strict lockdown that implied the closure of the entire educational system. From a systemic-family stress perspective, the impact of these changes might have consequences not only in each family member in isolation, but in the parental dynamic, and consequently in children's well-being. This paper presents the results of a follow-up study, evidencing changes in self-reported parental depression and perceived home organization of mothers and fathers during three different moments: before the pandemic, at the initial outbreak, and after one month of strict lockdown. Relevant moderators were explored using Linear Mixed Models to understand the within subjects’ changes of mothers' and fathers' self-report across the different times of the study. Financial strain, personality traits of self-criticism and dependency, previous parent-child quality interaction, recent major stressor events, and the number of children are recognized as relevant factors that moderate changes in home chaos and parental mental health perception. Therefore, significant risks and protective factors are highlighted for fathers, mothers, and parental dyads. Crucially, as the design of this study includes pre-pandemic measures as baseline levels, the results delimitate personal and family characteristics that were related to better outcomes. These results can contribute to understanding the impact of the sanitary regulations for relevant social contexts as the family system, giving indications of vulnerability characteristics that should be under consideration.